Abscisic Acid: Role in Fruit Development and Ripening - Gupta, Kapil; Wani, Shabir H.; Razzaq, Ali; Skalicky, Milan; Samantara, Kajal; Gupta, Shubhra; Pandita, Deepu; Goel, Sonia; Grewal, Sapna; Hejnak, Vaclav; Shiv, Aalok; El-Sabrout, Ahmed M.; et al. (Frontiers in Plant Science, 2022)
Abscisic acid (ABA) is a plant growth regulator known for its functions, especially in seed maturation, seed dormancy, adaptive responses to biotic and abiotic stresses, and leaf and bud abscission. ABA activity is governed by multiple regulatory pathways that control ABA biosynthesis, signal transduction, and transport. The transport of the ABA signaling molecule occurs from the shoot (site of synthesis) to the fruit (site of action), where ABA receptors decode information as fruit maturation begins and is significantly promoted. The maximum amount of ABA is exported by the phloem from developing fruits during seed formation and initiation of fruit expansion. In the later stages of fruit ripening, ABA export from the phloem decreases significantly, leading to an accumulation of ABA in ripening fruit. Fruit growth, ripening, and senescence are under the control of ABA, and the mechanisms governing these processes are still unfolding. During the fruit ripening phase, interactions between ABA and ethylene are found in both climacteric and non-climacteric fruits. It is clear that ABA regulates ethylene biosynthesis and signaling during fruit ripening, but the molecular mechanism controlling the interaction between ABA and ethylene has not yet been discovered. The effects of ABA and ethylene on fruit ripening are synergistic, and the interaction of ABA with other plant hormones is an essential determinant of fruit growth and ripening. Reaction and biosynthetic mechanisms, signal transduction, and recognition of ABA receptors in fruits need to be elucidated by a more thorough study to understand the role of ABA in fruit ripening. Genetic modifications of ABA signaling can be used in commercial applications to increase fruit yield and quality. This review discusses the mechanism of ABA biosynthesis, its translocation, and signaling pathways, as well as the recent findings on ABA function in fruit development and ripening.